Nd-Fe-B magnets under electron irradiation with the energy of 23 MeV - Bovda, V.A.; Bovda, А.М.; Guk, I.S.; Dovbnya, A.N.; Lyashchenko, V.N.; Mytsykov, A.O.; Onishchenko, L.V.; Каndybei, S.S.; Repikhov, О.А. (Вопросы атомной науки и техники, 2020)
Four Nd-Fe-B magnets underwent irradiation under 23 MeV electron beam. Nd-Fe-B magnets were magnetized to the technical saturation in the magnetic field of 3.5 T before electron treatment. Two Nd-Fe-B samples (1 and 2) were exposed to the direct electron beam with the energy of 23 MeV. Sample 2 was shielded by tungsten converter. The thickness of the tungsten converter was 4.72 mm. The absorbed dose for the samples was 16 GRad. Sample 3 was subjected to bremsstrahlung of electron irradiation with the energy of 23 MeV. Sample 4 was used as a reference sample for calibration and control measurements. While magnetic flux of sample under direct electron beam of 23 MeV was changed significantly, sample 2 showed the change of magnetic flux to a less degree. Magnetic performance of sample 3 corresponded closely to the initial state. Були проведені експериментальні дослідження поля чотирьох зразків магніту з Nd-Fe-B-сплаву, попередньо намагнічених в імпульсному магнітному полі 3,5 Тл. Зразки № 1 і 2 піддавалися прямій дії електронним пучком з енергією 23 МеВ. Перед зразком № 2 впритул містився конвертор з вольфраму товщиною 4,72 мм. Поглинена доза для зразків складала 16 Град. Зразок № 3 піддавався впливові гальмівного випромінювання електронним пучком з енергією 23 МеВ. Зразок № 4 не опромінювався і служив опорним еталоном для калібрування точності методу і контрольних вимірів. Спостерігається істотна зміна магнітного поля зразка № 1, що піддавався прямій дії електронним пучком з енергією 23 МеВ. У меншій мері ця зміна спостерігалася для зразка № 2. Поле навколо зразка № 3 практично не змінилося. Были проведены экспериментальные исследования поля четырёх образцов магнита из Nd-Fe-B-сплава, предварительно намагниченных в импульсном магнитном поле 3,5 Тл. Образцы № 1 и 2 подвергались прямому воздействию электронным пучком с энергией 23 МэВ. Перед образцом № 2 вплотную помещался конвертор из вольфрама толщиной 4,72 мм. Поглощённая доза для образцов составляла 16 Град. Образец № 3 подвергался воздействию тормозным излучением электронного пучка с энергией 23 МэВ. Образец № 4 не облучался и служил опорным эталоном для калибровки точности метода и контрольных измерений. Наблюдается существенное изменение магнитного поля образца № 1, подвергавшегося прямому воздействию электронным пучком с энергией 23 МэВ. В меньшей мере это изменение наблюдалось для образца № 2. Поле вокруг образца № 3 практически не изменилось.